Bottom–up trophic effects on fisher Pekania pennanti harvest age structure: associations with mast, voles and owls. Issue 4 (15th October 2021) - Greenhorn, Janet E.; Bowman, Jeff; Denomme-Brown, Simon T.; Ethier, Danielle M.
Abstract : Harvest management quotas for fishers Pekania pennanti in some jurisdictions are estimated from the previous year's harvest, and stem from the hypothesis that age ratios in the harvest are largely influenced by 'top–down' trapping pressure. The influence of 'bottom–up' food supply on fisher harvest age ratios might be underappreciated, which could result in a misallocation of quotas in management planning. We assessed a variety of data sources to test the influence of bottom–up processes on fisher populations in Ontario, Canada. We found evidence that bottom–up trophic effects influence the harvested fisher age structure in some regions of Ontario. Evidence also suggests that harvest pressure had little top–down influence on age ratios over the course of our study, and that basing management strategies on this assumption may lead to unintentional overharvest in years of low productivity. We suggest several trophic linkages with potential to facilitate fisher management, including connections among berry and seed crops, small mammals and northern saw‐whet owls Aegolius acadicus .